Social psychology of leader`s temporality in social projects - Radion Svynarenko; Rudska Antonina (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
The paper discusses the key socio-psychological characteristics of temporal potential leaders of social projects. It is shown that for different types of leaders in social projects (aimed at action, cooperation and development) respectively inherent specific time discourse.
Keywords: leadership; social projects; "perception" of time; speed; synchronization; time perspective